The Impact of Ambulance Diversion on Heart Attack Deaths - Natalia Yankovic; Sherry Glied; Linda V. Green; Morgan Grams (SAGE Publishing, 2010)
Hospital ambulance diversions are prevalent and increasing nationwide as emergency departments experience growing congestion. Using negative binomial regressions, this paper links the number of acute myocardial infarction (AMI) deaths to the level and extent of diversion in the five boroughs of New York City. The results indicate that both high levels of ambulance diversion and simultaneous diversion across hospitals are associated with increasing numbers of deaths from AMI.